Abuso sexual y factores emocionales que afectan a los niños y adolescentes de la “Fundación niños Queridos” de la parroquia Virginia del cantón Babahoyo provincia de los Ríos - Pazmiño Ramírez, Karem Nataly (2016)
The present study allowed the evaluation of sexual abuse traits in children and adolescents of the CHILDREN FOUNDATION, of the Virginia Parish of the Babahoyo Canton, Province of Los Ríos. Qualitative and quantitative methods were used for its execution. The type of research is descriptive, analytical and documentary. For its development, the psychological test, clinical history, interview, which contributed to the diagnosis was used. A sample of 20 were taken among children and adolescents who stay in the foster home, in the Psychological Clinic. The therapeutic, cognitive behavioral approach was adopted, covering several techniques of the most used in the play as a form of intervention and therapy, used stories, social skills training and problem solving, the elaboration of workshop talks and Psychoeducation Regarding the Theme and the disposition of an interdisciplinary team and the authorities that contribute many with the FUNIQUE. In the interviews applied to the children and adolescents it is determined that the sexual abuse according to the results obtained in the application of the clinical history 100% is male, 0% belong to female; Ages between 8 years with 53%, 12 years with 27% and 20% of them 14 years; Sexual abuse in dysfunctional households with 65% and 35% with functional households; Poor interpersonal relationships with 25%, good relationship with 15% and 60% with a regular relationship, which if not treated can significantly affect the social, academic and work area of the FUNIQUES